'It was like he was in the room with us': patients' and carers' perspectives of telemedicine in acute stroke. (8th January 2015) - Gibson, Josephine; Lightbody, Elizabeth; McLoughlin, Alison; McAdam, Joanna; Gibson, Alison; Day, Elaine; Fitzgerald, Jane; May, Carl; Price, Chris; Emsley, Hedley; Ford, Gary A; Watkins, Caroline
Abstract: Background: Telemedicine can facilitate delivery of thrombolysis in acute stroke. The aim of this qualitative study was to explore patients' and carers' views of their experiences of using a stroke telemedicine system in order to contribute to the development of reliable and acceptable telemedicine systems and training for health‐care staff. Method: We recruited patients who had, and carers who were present at, recent telemedicine consultations for acute stroke in three hospitals in NW England. Semi‐structured interviews were conducted using an interview guide based on normalization process theory (NPT). Thematic analysis was undertaken. Results: We conducted 24 interviews with 29 participants (16 patients; 13 carers). Eleven interviews pertained to 'live' telemedicine assessments (at the time of admission); nine had mock‐up telemedicine assessments (within 48 h of admission); four had both assessments. Using the NPT domains as a framework for analysis, factors relating to coherence (sense making) included people's knowledge and understanding of telemedicine. Cognitive participation (relational work) included interaction between staff and with patients and carers. Issues relating to collective action (operational work) included information exchange and support, and technical matters. Findings relating to reflexive monitoring (appraisal) included positive and negative impressions of the telemedicine process, and emotional reactions. Conclusion: Although telemedicine was well accepted by many participants, its use added an additional layer of complexity to the acute stroke consultation. The 'remote' nature of the consultation posed challenges for some patients. These issues may be ameliorated by clear information for patients and carers, staff interpersonal skills, and teamworking.